Info Kampus Isu 25 // Universiti Teknologi MARA Sarawak - Universiti Teknologi MARA Sarawak, Kampus Samarahan (Universiti Teknologi MARA Cawangan Sarawak, 2003)
Pemangku Timbalan Pengarah HEP Prof. Madya Dr Abang Ahmad Riazuan Abang Awit In Malaysia, we are very fortunate. We enjoy the luxury of a peaceful and secure environment where we can go about achieving our individual and national dreams and aspirations without big disruptions. We must always remember that this luxury is the result of political stability and social security care fully maintained by the government. Security should never be taken for granted, be it security in our home, study or workplace or even our playground. Without security there can be no progress, no happiness, so we should always be actively con cerned about security, not only in our immediate surroundings, but in the country as a whole and even at the international level. We must be always on guard to prevent distruptions to the peace that we need for a harmonious and progressive life.